Pengaruh Pengembangan Karir, Work Life Balance, dan Lingkungan Kerja terhadap Loyalitas Pegawai (Studi pada Kantor Kecamatan Pondok Aren di Kota Tangerang Selatan) - Binsar Fauzan Supriyadi; Zulvia Khalid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to determine the effect of Career Development (X1) on Employee Loyalty (Y), Work-Life Balance (X2) on Employee Loyalty (Y), and Work Environment (X3) on Employee Loyalty (Y) among Employees of Pondok Aren Subdistrict in South Tangerang City. It uses Non-Probability Sampling technique with a saturated method. The population in this study consists of 64 employees who are part of the Employees of Pondok Aren Subdistrict in South Tangerang City. The sample in this study consists of 64 respondents. This research was conducted using multiple linear regression methods assisted by SPSS version 25 and Microsoft Excel 2019. The results show that Career Development (X1) has a Positive and Significant effect on Employee Loyalty (Y), Work Life Balance (X2) has a Positive and Significant effect on Employee Loyalty (Y), and Work Environment (X3) has a Positive and Significant effect on Employee Loyalty (Y).